2006
DOI: 10.1111/j.1464-5491.2006.01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Established diabetic neuropathy seems irreversible despite improvements in metabolic and vascular risk markers—a retrospective case–control study in a hospital patient cohort

Abstract: Data on reversibility of neuropathy are scarce and our 8-year series shows a continual deterioration in VPT in patients with a threshold > 25 V despite modest improvements in glycaemic control and lipid parameters. This work also supports a vascular association with neuropathy and identifies neuropathic patients as a high-risk cardiovascular group in whom, despite little influence on neuropathy itself, the above metabolic factors should be actively addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Despite this, five patients developed an ulcer in a short span of 9 months. This is not surprising as available literature shows similar results [14] and may be related to the long duration of the previous glycaemic burden.…”
Section: Discussionsupporting
confidence: 71%
“…Despite this, five patients developed an ulcer in a short span of 9 months. This is not surprising as available literature shows similar results [14] and may be related to the long duration of the previous glycaemic burden.…”
Section: Discussionsupporting
confidence: 71%
“…Contrary to observations made in cohort studies [2,13], improvements in neuropathic symptoms as well as deficits measured by objective tests have been observed in the placebocontrolled groups of clinical trials examining therapeutic agents for diabetic neuropathy [4][5][6][7][8][9][10][11][19][20][21][22]. For example, phase III studies of the protein kinase Cb inhibitor ruboxistaurin revealed significant improvements over 1 year in subjects receiving placebo in two common clinical scales, as well as in quantitative sensory testing [10].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective data indicate that multifactorial cardiovascular risk intervention may be more successful in diabetic patients without than in those with polyneuropathy (Coppini et al, 2006), although recent controlled clinical trials could not demonstrate a favourable effect of multifactorial intervention or intensive diabetes therapy on new or worsening neuropathy in Type 2 diabetic patients (Gaede et al, 2008;The ADVANCE Collaborative Group, 2008). An important risk factor associated with diabetic peripheral neuropathic pain is waist circumference and low physical activity, while peripheral arterial disease is a relevant associated disorder.…”
Section: Discussionmentioning
confidence: 99%